Respostas
respondido por:
1
Resolução
- 10 + x = 3x + 2
x - 3x = 2 + 10
- 2x = 12
x = 12/-2
x = - 6
- 10 + x = 3x + 2
x - 3x = 2 + 10
- 2x = 12
x = 12/-2
x = - 6
amandamoschenou15uz:
-10+x= 3x+x
respondido por:
1
-10+x=3x+2
x-3x=2+10
-2x=12
x=12/-2
x=-6
Quaisquer duvidas referentes a resposta em questão estou inteiramente a disposição para esclarecimento.
x-3x=2+10
-2x=12
x=12/-2
x=-6
Quaisquer duvidas referentes a resposta em questão estou inteiramente a disposição para esclarecimento.
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás